Accounting students perception on Online Homework Software (OHS) - Muhamad, Haslinah; Osman, Mohammad Noor Hisham; Mustafa, Hasri; Abdul Razak, Abdul Razif (Penerbit Akademia Baru, 2015)
Recent technologies provide variety of tools for educators in all field including accounting. One of these tools is Online Homework Software (OHS). This study collects survey data from accounting students at Universiti Putra Malaysia to explore their perception of OHS in accounting courses. Analysis of the survey data indicated several differences between OHS users and nonusers. There are a positive correlation between shorterm performance and the hours spent of revision to the use of OHS. The ANOVA analysis show no significant difference in current CGPA (long term performance) between OHS users and nonusers. The users of OHS have reveal that the educators using OHS for assigned graded homework and the quizzes but not using OHS for formal exam. The user of OHS agree that OHS will give benefit in accounting course and able to reduce time spent in revision. Respondents also belief that OHS is a cost effective learning tool. However, the strongest concern express by the respondents is whether the use of OHS really improves their learning. The data collected is important in promoting dialog concerning OHS usage and developing recommendations for continued improvements in the software.